Platelet dysfunction in thrombosis patients treated with vitamin K antagonists and recurrent bleeding. - Paola E J van der Meijden; Annemieke C Bouman; Marion A H Feijge; René van Oerle; Henri M H Spronk; Karly Hamulyák; Arina J ten Cate-Hoek; Hugo ten Cate; Johan W M Heemskerk (PLoS ONE, 2013)
BACKGROUND: Recurrent bleeding can complicate the treatment of thrombosis patients with vitamin K antagonists (VKA), even at a well-regulated level of anticoagulation. In this proof-of-principle study, we investigated whether alterations in platelet function or von Willebrand factor (vWf) contribute to a bleeding phenotype in these patients. METHODS: In this case-control study 33 well-regulated patients without bleeding events (controls) and 33 patients with recurrent bleeding (cases) were retrospectively included. Thrombin generation and vWf were determined in plasma. Platelet function was assessed by light transmission aggregometry and flow cytometry using a validated panel of agonists. RESULTS: Thrombin generation was similarly reduced in controls and cases, in comparison to normal plasma. Plasma vWf level was above the normal range in 85% of controls and 67% of the cases. vWf activity was similarly increased in all patients in comparison to healthy volunteers. Platelet aggregation was in the normal range for almost all patients irrespective of the type of agonist. However, in response to a low collagen dose, platelets from 21% of controls and 27% of cases showed diminished responses. Agonist-induced secretion of alpha- and dense-granules or integrin αIIbβ3 activation were affected in platelets from neither controls nor cases. CONCLUSION: Recurrent bleeding in well-controlled patients on VKA therapy is not explained by anti-hemostatic changes in platelet or vWf function.